Regulated cell death mechanisms and their crosstalk with the immune system 2 - Baena-Lopez, Luis Alberto (Henry Stewart Talks, 2020)
Crosstalk between the RCD mechanisms and the immune response, Immunological cell death vs. other forms of RCD, Immune system factors that are involved in cell death, Self-tolerance and immunogenicity, Immunogenic cell death and cancer therapy